Fasciolosis dan Cryptosporidiosis pada Ternak Sapi di Desa Maranatha, Kabupaten Sigi, Sulawesi Tengah - Samarang Samarang; Junus Widjaja; Primasari Primasari; Muchlis Syahnuddin (Jurnal Vektor Penyakit, 2022)
ABSTRACT Fasciolosis and Cryptosporidiosis are zoonotic parasitic diseases. Fasciolosis in Indonesia is caused by the trematode worm Fasciola gigantica species and generally attacks ruminants, while cryptosporidiosis is caused by the protozoan species Cryptosporidium parvum as a source of diarrheal disease infection. The purpose of the study was to identify fasciolosis and cryptosporidiosis infections in cattle in Maranatha Village, Sigi District, Central Sulawesi which was carried out for four months. The research design was cross-sectional with the determination of the sample using a purposive sampling method. The research sample was feces from cattle aged 6 months–2 years. The collected samples were prepared using the formalin ether sedimentation method. The results of 62 stool samples identified fasciolosis and cryptosporidiosis infections in cattle in Maranatha village, namely 38.7% and 14.52%, respectively. Conclusions: More than one-third of the cows examined were infected with fasciolosis and about a quarter of the cows examined were infected with C. parvum. Suggestions should be regular supervision or monitoring of the provision of deworming drugs to livestock, as well as counseling supervision and provision of clean water sources for the local community. ABSTRAK Fasciolosis dan cryptosporidiosis merupakan penyakit parasiter bersifat zoonosis. Fasciolosis di Indonesia disebabkan oleh cacing trematoda spesies Fasciola gigantica dan umumnya menyerang ternak ruminansia, sedangkan cryptosporidiosis disebabkan oleh protozoa spesies Criptosporodium parvumsebagai sumber infeksi penyakit diare. Tujuan penelitian yaitu mengidentifikasi infeksi fasciolosis dan cryptosporidiosis pada sapi di Desa Maranatha, Kabupaten Sigi, Sulawesi Tengah yang dilaksanakan selama empat bulan. Disain penelitian adalah cross sectional dengan penentuan sampel menggunakan metode purposive sampling. Sampel penelitian adalah tinja dari ternak sapi yang berumur 6 bulan–2 tahun. Sampel yang terkumpul dipreparasi menggunakan metode sedimentasi formalin eter. Hasil dari 62 sampel tinja teridentifikasi infeksi fasciolosis dan cryptosporidiosis pada sapi di Desa Maranatha yaitu sebesar 38,7% dan 14,52%. Kesimpulan lebih dari sepertiga jumlah sapi yang diperiksa terinfeksi fasciolosis dan sekitar seperempat dari sapi yang diperiksa ternfeksi C. parvum. Saran sebaiknya ada pengawasan atau pemantauan secara berkala pada pemberian obat cacing pada ternak, serta penyuluhan, pengawasan dan pengadaan sumber air bersih untuk masyarakat setempat.